MetaDAVis: An R shiny application for metagenomic data analysis and visualization - Sankarasubramanian Jagadesan; Chittibabu Guda (PLoS ONE, 2025)
The human microbiome exerts tremendous influence on maintaining a balance between human health and disease. High-throughput sequencing has enabled the study of microbial communities at an unprecedented resolution. Generation of massive amounts of sequencing data has also presented novel challenges to analyzing and visualizing data to make biologically relevant interpretations. We have developed an interactive Metagenome Data Analysis and Visualization (MetaDAVis) tool for 16S rRNA as well as the whole genome sequencing data analysis and visualization to address these challenges using an R Shiny application. MetaDAVis can perform six different types of analyses that include: i) Taxonomic abundance distribution; ii) Alpha and beta diversity analyses; iii) Dimension reduction tasks using PCA, t-SNE, and UMAP; iv) Correlation analysis using taxa- or sample-based data; v) Heatmap generation; and vi) Differential abundance analysis. MetaDAVis creates interactive and dynamic figures and tables from multiple methods enabling users to easily understand their data using different variables. Our program is user-friendly and easily customizable allowing those without any programming background to perform comprehensive data analyses using a standalone or web-based interface.